Cytotoxic Potential of Arthrospira platensis Extract on Cervical Cancer Cells Line Hela: Study on Antiproliferative, Cell Cycle, Apoptosis Induction and Anti Metastasis - Laela Hayu Nurani; Nurkhasanah Mahfudh; Ibnu Gholib Gandjar; Intan Rahayu (Indonesian Journal of Pharmacy, 2020)
Cervical cancer can be treated conventionally with chemotherapy agents, but its use has side effects and complications in the form of damage to normal cells. This study aims to determine the potential of A. platensis as an alternative anticancer agent that is selective towards normal cells. Based on TLC analysis, A. platensis contains antioxidant compounds such as β-carotene, flavonoids, and terpenoids which are able to inhibit proliferation and trigger apoptosis of cancer cells. The study was conducted using cervical cancer cells HeLa and normal cells HDFa. A. platensis macerated with 96% ethanol at a ratio of 1:4. Based on probit analysis, it is known that ethanol extract of A. platensis has a cytotoxic effect on HeLa cells with IC50 values of 260.444μg/mL and index selectivity towards HDFa cells of 7.931. The mechanism of cytotoxic activity of ethanol extract of A. platensis is related to its ability to extend the doubling time, increase the induction of apoptosis, and reduce the rate of cells migration. Ethanol extract of A. platensis can also increase cells accumulation in the S phase to prevent cells from entering the G2/M phase.